Perilaku Bullying pada remaja kelas XI SMAN 21 Surabaya: Bagaimana Kecenderungan Pola Asuh Otoriter dan Regulasi Emosi? - Sari, Annisa Permata; Sukiatni, Dwi Sarwindah; Rina, Amherstia Pasca (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Adolescence is a transition period in children's development. In fact, many teenagers are not yet able to undergo this stage of development, so many of them commit delinquency, such as bullying. This research aims to determine the relationship between authoritarian parenting and emotional regulation and the tendency to engage in bullying behavior in adolescents. The population in this study was 380 class XI students of SMA Negeri 21 Surabaya. The population in this study was 191 class XI students at SMA Negeri 21 using the Krejcie table. The method for analyzing correlational data was with the help of IBM SPSS version 25 for Windows and the simultaneous test results showed a significance of 0.000 (p<0.05). This means that authoritarian parenting and emotional regulation influence the tendency to carry out bullying behavior. In the partial test, there is a significant influence between bullying and authoritarian parenting with a significance value of <0.001 (p<0.05) and bullying and emotional regulation with a significance value of <0.001 (p<0.05), meaning there is a significant relationship between authoritarian parenting and emotional regulation. with a tendency to carry out bullying behavior in teenagers.